Comparison of Learning Outcomes of Students taught Using Quantum Teaching Models with Direct Learning Models on the Main Sub-Matter of the Human Respiration System at Muhammadiyah Rappang High School - Madaling Madaling; Sam Hermansyah; Usman M; Khaeriyah Adri; Hasan Hasan (Universitas Muhammadiyah Enrekang, 2024)
This research aims to find out which learning model is best to use between Quantum Teaching and Direct Instruction on the main sub-subject of the Human Respiration System. This research was carried out on 11-30 August 2022, where the research was carried out at SMA Muhammadiyah Rappang. The population of this research was all class XI students consisting of two classes, with a sample of 80 people. Sampling was carried out using Total Sampling. The instruments used in this research were the Learning Implementation Plan (RPP) and tests in the form of questions about the Human Respiration System. Evaluation is carried out by giving a multiple choice test with 20 questions. Data were analyzed using the t test. The results of the research show that the learning outcomes of students who were taught using the Quantum Teaching Learning Model in the main sub-material of the Human Respiration System in class . The learning outcomes of students who were taught using the Direct Instruction Model on the main sub-material of the Respiration System in Humans in class Thus, the learning outcomes of students taught using the Quantum Teaching Learning Model with the Direct Instruction Model on the main sub-material of the Respiration System in Humans in class namely 4.4 > 1.994 so it can be concluded that the Ho Hypothesis is rejected and the Ha Hypothesis is accepted, meaning that there is a difference in student learning outcomes taught using the Quantum Teaching Learning Model and the Direct Instruction Model in class XI of SMA Muhammadiyah Rappang for the 2022/2023 academic year.